Bosnian Muslims (Boshniaks) towards the NDH state and the Ustasha movement - Gucka, Agnieszka (Balcanica Posnaniensia. Acta et studia, 2009)
This article analyses the attitude of Bosnian Muslims towards the Ustasha movement and the establishment of the Independent State of Croatia (NDH, 1941). In Ustasha propaganda, Bosnian Muslims were presented as ‘the purest Croats’, which was supposed to ensure their inclusion in the socio-political structures of the NDH. The aim of the study is to show the reaction of the Muslim community towards the NDH and to answer the question of to what extent it accepted the Ustasha national-political project. The study is based on propaganda documents of the NDH authorities, resolutions of Muslim communities and historiographical studies. The author uses the method of source analysis and a critical approach to historical narrative. The research findings indicate that although some Bosnian Muslims – especially the elites associated with the Yugoslav Muslim Organisation – initially accepted the NDH as a lesser evil compared to the previous Serbian domination, tensions and disappointments quickly emerged. Muslim participation in the structures of the NDH was limited, and the declared equality with Catholics was mostly symbolic. Among Muslims, autonomist initiatives and activities aimed at self-defence or supporting the communist guerrilla movement grew. The Ustasha policy towards Muslims ended in failure. Instead of becoming a pillar of the NDH, this community largely became a victim of repression, which strengthened their sense of separateness.